TRIP/NOPO E3 ubiquitin ligase promotes ubiquitylation of DNA polymerase ?. - Wallace, H.A.; Merkle, J.A.; Yu, M.C.; Berg, T.G.; Lee, E.; Bosco, G.; Lee, L.A. (Development, 2014)
We previously identified a Drosophila maternal effect-lethal mutant named 'no poles' (nopo). Embryos from nopo females undergo mitotic arrest with barrel-shaped, acentrosomal spindles during the rapid cycles of syncytial embryogenesis because of activation of a Chk2-mediated DNA checkpoint. NOPO is the Drosophila homolog of human TNF receptor associated factor (TRAF)-interacting protein (TRIP), which has been implicated in TNF signaling. NOPO and TRIP contain RING domains closely resembling those of known E3 ubiquitin ligases. We herein sought to elucidate the mechanism by which TRIP/NOPO promotes genomic stability by performing a yeast two-hybrid screen to identify potential substrates/interactors. We identified members of the Y-family of DNA polymerases that facilitate replicative bypass of damaged DNA (translesion synthesis) as TRIP interactors. We show that TRIP and NOPO co-immunoprecipitate with human and Drosophila Pol?, respectively, from cultured cells. We generated a null mutation in Drosophila Pol? (dPol?) and found that dPol?-derived embryos have increased sensitivity to ultraviolet irradiation and exhibit nopo-like mitotic spindle defects. dPol? and nopo interact genetically in that overexpression of dPol? in hypomorphic nopo-derived embryos suppresses nopo phenotypes. We observed enhanced ubiquitylation of Pol? by TRIP and NOPO E3 ligases in human cells and Drosophila embryos, respectively, and show that TRIP promotes hPol? localization to nuclear foci in human cells. We present a model in which TRIP/NOPO ubiquitylates Pol? to positively regulate its activity in translesion synthesis.